Indisciplina em sala de aula: uma análise funcional - Martins, Ana Helena Lanhoso (2018)
Classroom misbehavior is one of the main teachers’ complaints regarding problems they face within the school. When it happens too often, misbehavior not only detract from learning in class but also make the teacher’s work in the classroom unfeasible. The aim of this study was to identify the types and frequency of classroom misbehavior, situations in which such behaviors are emitted the most and the way teachers act facing them. The present research was carried out with a 9th grade class Elementary School II in a municipal school in São Paulo and consisted in an observation of mathematics classes (with holder and substitutes), history, reading room and geography. Among the results, it was identified that more than half of the episodes observed had a misconduct. Most frequent ones were; talk, handle cell phone and stand/walk around the room, and less frequent were; apply makeup, throw things on someone and sing. Most of the episodes with indiscipline, teachers did not release any consequences for this students, and the subjects in which teachers did not release any consequences for them (history and mathematics with substitutes) their frequency was higher, and in the subjects which the teachers most consequence them (geography and mathematics with holder) their frequency was lower. It was also found that the aversive consequences released by teachers for the misbehavior had only immediate effect, however, it was verified that teachers’ practices that engaged the students in the proposed activities were more efficient to weaken misbehavior. Thus, it is concluded that in order to have a better control of indiscipline, it is important that teachers have a repertoire of practices that create favorable conditions for students' learning and engagement in the classroom